Transcriptional response to 131I exposure of rat thyroid gland - Rudqvist, Nils; Spetz, Johan; Schüler, Emil; Parris, Toshima Z.; Langen, Britta; Helou, Khalil; Forssell-Aronsson, Eva (PLOS ONE, 2017)
Humans are exposed to 131I in medical diagnostics and treatment but also from nuclear accidents, and better knowledge of the molecular response in thyroid is needed. The aim of the study was to examine the transcriptional response in thyroid tissue 24 h after 131I administration in rats. The exposure levels were chosen to simulate both the clinical situation and the case of nuclear fallout. Thirty-six male rats were i.v. injected with 0–4700 kBq 131I, and killed at 24 h after injection (Dthyroid = 0.0058–3.0 Gy). Total RNA was extracted from individual thyroid tissue samples and mRNA levels were determined using oligonucleotide microarray technique. Differentially expressed transcripts were determined using Nexus Expression 3.0. Hierarchical clustering was performed in the R statistical computing environment. Pathway analysis was performed using the Ingenuity Pathway Analysis tool and the Gene Ontology database. T4 and TSH plasma concentrations were measured using ELISA. Totally, 429 differentially regulated transcripts were identified. Downregulation of thyroid hormone biosynthesis associated genes (e.g. thyroglobulin, thyroid peroxidase, the sodium-iodine symporter) was identified in some groups, and an impact on thyroid function was supported by the pathway analysis. Recurring downregulation of Dbp and Slc47a2 was found. Dbp exhibited a pattern with monotonous reduction of downregulation with absorbed dose at 0.0058–0.22 Gy. T4 plasma levels were increased and decreased in rats whose thyroids were exposed to 0.057 and 0.22 Gy, respectively. Different amounts of injected 131I gave distinct transcriptional responses in the rat thyroid. Transcriptional response related to thyroid function and changes in T4 plasma levels were found already at very low absorbed doses to thyroid.